Midwives Experiences of Managing Clients with Eclampsia in a low Resource Setting: A Qualitative Descriptive Study - Anita Fafa Dartey PhD, MNurs, OHN, RN; Gladys Dzansi PhD, MPhil, RN; Comfort Worna Lotse MPhil, BPH, RN; Racheal Obuobisa BSc, RM; Celestine Emefa Afua Bosu BSc, RM; Agani Afaya MSc, BSc, RN (SAGE Publishing, 2022)
Objective Eclampsia remains a public health issue, especially in low-resource countries worldwide. Midwives are the backbone of the pregnancy and delivery process. Midwives trained in the necessary knowledge and skills are more likely to notice early warning signals of preeclampsia and immediately help clients in such emergencies. This study explored midwives' experiences in managing patients with eclampsia in Ghana. Methods This study was conducted among eight registered midwives at maternity units of two district hospitals in the Eastern Region of Ghana, using an exploratory, descriptive qualitative research design. A purposive sampling technique was adopted to select and interview participants. Interviews were audio-recorded, transcribed, and analyzed using qualitative thematic analysis. The right of participation and withdrawal from the study was respected. Findings The three emerged overriding themes are: 1. Midwives have knowledge (warning signs, regimens, and prevention of complications) about the management of eclampsia. 2. Challenges in managing clients included inadequate equipment, staffing, and access to drugs. 3. Strategies for mitigating barriers to care for women with eclampsia (adherence to protocols, teamwork, peer mentoring and supervision, midwives' attitude, and client education. Conclusion Midwives working in underserved facilities have the knowledge and skill to monitor and manage pregnant women experiencing eclampsia. However, they need to be supported with appropriate resources and advanced equipment to ensure adherence to protocols on managing eclampsia promptly referred. Continuous training and workshops for midwives in the management of hypertension in pregnancy are recommended and the public educated on the dangers of eclampsia.